Corridas de aventura: processos de coesão grupal na superação de obstáculos - Moretti, Alexandre Roberto (2009)
The subject this research are the social relations and more specifically the relationship between athletes practicing a team adventure race, with reference to group cohesion. Permeating social relations and social practices (adventure racing) have, contemporaneously, the risks and other consequences of late modernity, which in turn causes each person deal differently. Some people will be prevented, some avoidable and others will check the risk, either in their productive time, they are working or in their spare time, in hours of leisure and sports activities. Currently, the racing is the leading exponent of the practices that actively seek risk, the risk-adventure. Adventure racing originated in the contemporary context, and nowadays can be considered one of the riskiest practices and extreme - has a long way with about 500 km, crossing places unexplored and inhospitable, subjected to various omens of nature, in a contest to realize the course in less time, and often without sleep (no stop). Due to its characteristics, its regulation and, as a safety measure, the racing is done in teams, forcing athletes to relate to overcome various obstacles and achieve their goals. Thus, keep the team united and cohesive it becomes necessary. Understand how the players relate to overcome obstacles, to maintain the unity and cohesion, it was possible through interviews and follow-up as a team member in support of a team that participated in a race that was the scene of world championship racing adventure 2008, resulting in notes in a diary, which was used to obtain context data. The interviews were conducted individually with each athlete before the race and after the race, an interview with the four players together. The results showed that athletes attribute the sense of group cohesion to the three main dimensions: communication, help/support each other and keep the pace. And when there is a provision for group cohesion in the face of danger/risk, the team tends to unite and become more cohesive. The three dimensions are not independent and the link is the interaction. The interaction between team members must provide the means to negotiate, exchange and give directions, both individual and group on the task and the emotions generated by the tasks